Impact of temperature-dependent phage expression on Pseudomonas aeruginosa biofilm formation - Karishma Bisht (Nature Portfolio, 2021)
Abstract Pseudomonas aeruginosa is a ubiquitous opportunistic pathogen that forms robust biofilms in the different niches it occupies. Numerous physiological adaptations are required as this organism shifts from soil or aquatic environments to a host-associated lifestyle. While many conditions differ between these niches, temperature shifts are a factor that can contribute to physiological stress during this transition. To understand how temperature impacts biofilm formation in this pathogen, we used proteomic and transcriptomic tools to elucidate physiological responses in environment-relevant vs. host-relevant temperatures. These studies uncovered differential expression of various proteins including a phage protein that is associated with the EPS matrix in P. aeruginosa. This filamentous phage was induced at host temperatures and was required for full biofilm-forming capacity specifically at human body temperature. These data highlight the importance of temperature shift in biofilm formation and suggest bacteriophage proteins could be a possible therapeutic target in biofilm-associated infections.